1995
DOI: 10.1016/0393-0440(94)00038-6
|View full text |Cite
|
Sign up to set email alerts
|

Geometry of Higgs and Toda fields on Riemann surfaces

Abstract: We discuss geometrical aspects of Higgs systems and Toda field theory in the framework of the theory of vector bundles on Riemann surfaces of genus greater than one. We point out how Toda fields can be considered as equivalent to Higgs systems -a connection on a vector bundle E together with an End(E)-valued one form both in the standard and in the Conformal Affine case. We discuss how variations of Hodge structures can arise in such a framework and determine holomorphic embeddings of Riemann surfaces into loc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(42 citation statements)
references
References 38 publications
2
40
0
Order By: Relevance
“…Since the moduli of these spaces correspond to variation of Hodge structures [9,15], there must exist a description of these structures directly in the higher dimension. This can be done via Higgs bundles in higher dimensions which has been studied by Simpson [28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the moduli of these spaces correspond to variation of Hodge structures [9,15], there must exist a description of these structures directly in the higher dimension. This can be done via Higgs bundles in higher dimensions which has been studied by Simpson [28].…”
Section: Discussionmentioning
confidence: 99%
“…But their work does not seem to be related to the Fuchsian uniformisation presented in this paper. 3 Alvarez-Gaumé discusses 3 The difference can be seen by considering the well understood case of Fuchsian uniformithe problem of uniformisation in his ICTP lectures [14] and more recently, Aldrovandi and Falqui have also attempted to understand uniformisation using period maps [15].…”
Section: Introductionmentioning
confidence: 99%
“…Let C be a compact Riemann surface of genus g > 1. It has been shown that (1.1) defines a holomorphic connection on the vector bundle E = J n−1 (K C − n−1 2 ) of (n − 1)-jets of holomorphic sections of K C − n−1 2 , where K C is the canonical line bundle [3,16]. On the other hand, (1.2) defines a meromorphic connection on the vector bundle E = n−1 r=0 K C − n−1 2 +r [1,17].…”
Section: One Is Typically Interested In a Local Basis Of Flat Sectionsmentioning
confidence: 99%
“…We consider the pair (E, ∇) where E → C is the jet-bundle mentioned before. It is determined by the following condition [3]. Let us temporarily append the subscript "n", so that E (n) ≡ E; then E n is characterized as the extension…”
Section: Some Constructionsmentioning
confidence: 99%
See 1 more Smart Citation